Investigation of the Relationship between Red Blood Cell Profiles and Electrocardiographic Changes in Dogs with Parvoviral Enteritis - Sagkan Ozturk, Aliye; Boluk, Gizem Seyma (The Iraqi Journal of Veterinary Medicine, 2025)
Canine parvoviral enteritis (CPE) is a common viral disease in puppies that frequently results in severe gastrointestinal, hematological, and cardiac effects. This study aimed to look into the relationship between red blood cells parameters and ECG abnormalities, pointing out a potential connection between hematological changes and cardiac involvement in CPE. A total of 32 dogs of different breeds were incorporated in the data collected from animal hospital and classified into two main groups: 25 puppies with parvoviral enteritis and 7 healthy controls. The diseased group was divided into three subgroups based on ages and status of vaccination. Group 1: Eight puppies without vaccinations under 3 months of age; Group 2: Nine puppies without vaccinations over 3 months of age; Group 3: Eight puppies that had received vaccine but tested positive for parvovirus. Group I had microcytic hypochromic anemia and a significantly reduced hematocrit (%). Group I higher heart rate and shorter QT interval on the ECG were connected to red blood cell indices such as MCV, RDW, and MCH. Significant correlations were also established between the PR interval and RDW and between the QT/QTc interval and RDW, MCV, and MCH. In conclusion, this study revealed that hematological changes associated with canine parvoviral enteritis—especially changes in red blood cell indices such as RDW, MCV, and MCH—are strongly connected with electrocardiographic alterations. These results put forward that the change of these blood parameters could be created to variations in cardiac electrical activity during CPE. Accurate treatment strategies and monitoring of severity may be aided by an understanding of these links. Further studies are required to clarify the clinical usefulness of these hematological parameters as potential biomarkers in systemic viral infections‎‎‎.